B-cell depletion in the treatment of pemphigus: two clinical cases and literature review - Oleg V. Karzanov; Ekaterina V. Chernyaeva; Anna G. Kupriyanova; Yulia V. Molochkova; Elena V. Zenkevich; Anton V. Molochkov (Alʹmanah Kliničeskoj Mediciny, 2023)
Pemphigus presents a group of chronic autoimmune bullous skin disorders with well-known clinical signs, which pathophysiology is mediated by antibodies to various epidermal self-antigens. For a long time, the only therapeutic option for this disease was the lifelong use of non-selective immunosuppressive agents limited by high rate of severe adverse reactions. The article presents two clinical cases of rituximab use (a targeted agent leading to B-cell depletion) in patients with pemphigus (vulgaris and foliaceous) who were previously resistant to high-dose steroid therapy. Treatment with rituximab lead to response and allowed to decrease the prednisone dose in both cases. These results confirm that rituximab can be successfully used in pemphigus as adjuvant therapy if conventional agents for this dermatosis are ineffective.